(untitled) (Research, Society and Development, 2022)
It is not necessary a thorough and comprehensive search in databases to see that the seminal studies on the growth of the firm are focused on and guided by the viewpoint of the large company, the bearer of an organized structure and a defined hierarchy. This context reinforces the need to broaden the academic view of the small company, which has become an important figure in economies worldwide. Generally composed of conservative management in the growth process, small entrepreneurs diversify their product and service portfolio based on their previous experience and learning to ensure the subsistence of families and lives. Thus, this Systematic Review aims to enable and foster the study of small businesses seeking to understand what the literature discusses and presents about the growth of small businesses based on corporate diversification. Thus, by using keywords in two major databases, it was possible to verify the evolution of the concept of growth over time, identify different components that influence the growth of small businesses, as well as identify several aspects addressed by the literature in relation to the small business and its respective expansion.